2011
DOI: 10.1111/j.1365-2567.2011.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient modification within a pool of CD4 T cells in the maternal spleen

Abstract: Summary Classic models suggest maternal tolerance is dependent on regulation of fetal antigen‐specific T cell responses. We hypothesize that factors unique to a particular fetal antigen‐specific T cell, rather than the state of pregnancy per se, are important determinants of T cell fate during pregnancy. To investigate the fate of fetal antigen‐specific CD4 T cells in the systemic circulation, we examined spleen cells in a CD4 T cell receptor transgenic mouse specific for the male antigen H‐Y. We observed a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Within the T cell pool, we also found that both splenic CD4 (Bonney et al, 2011) and CD8 T cells (Norton et al, 2010) undergo a period of enhanced proliferation during normal gestation. Because PD-1 signaling is thought to play an important role in T cell homeostasis by limiting the expansion of activated cells, we hypothesized that pregnancy should alter the expression of Pd-1 in the spleen.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Within the T cell pool, we also found that both splenic CD4 (Bonney et al, 2011) and CD8 T cells (Norton et al, 2010) undergo a period of enhanced proliferation during normal gestation. Because PD-1 signaling is thought to play an important role in T cell homeostasis by limiting the expansion of activated cells, we hypothesized that pregnancy should alter the expression of Pd-1 in the spleen.…”
Section: Resultsmentioning
confidence: 55%
“…This is likely related to increased expression of receptors to cytokines, such as interleukin 7 and interleukin 15, that are known to support homeostatic proliferation. This turnover is also likely driven by increased expression of both pro and anti apoptotic genes (Norton et al, 2010) and related to exposure and recognition of male-specific antigens (Bonney et al, 2011; Lissauer et al, 2012). Homeostatic proliferation in response to chronic antigen stimulation can to lead to “exhaustion”, marked by expression of a discreet set of genes and decreased immune function (Wherry et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] We have studied T-cell homeostasis in mice and observed changes in the maternal immune system that persist PP. [21][22][23][25][26][27] There may be accumulation of TREGs in PP that may protect subsequent pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Since then several investigators have produced evidence in these systems that the maternal T cells are “aware” that the host is pregnant (Bonney, et al 2011), undergo proliferation and death (Norton, et al 2010) and are able to respond to fetal antigens (Erlebacher, et al 2007, Norton, et al 2010). For most mice, neither the increased presence of T cells specific for fetal antigen nor manipulations to increase fetal antigen specific T cell proliferation or function has resulted in specific pregnancy loss (see review by Moldenhauer, et al 2010).…”
Section: Introductionmentioning
confidence: 99%